Evaluation of Indigenous Knowledge and Fuel Value Index of Some Selected Sudano-Sahelian Fuelwood Species in Damaturu, Yobe State of Nigeria - Dadile, A. M.; Sotannde, O. A. (Advanced Aspects of Engineering Research Vol. 3, 2021)
Fuelwood utilization in the sudano-sahelian region requires massive felling of tree species which in turn resulted to deforestation and sand dunce couple with scarce vegetation in the region. Moreover, fuelwood is not only used for domestic and commercial purposes but for livelihood sustenance. However, the increase in demand and intensity of fuelwood resulted to indiscriminate felling of trees species for energy use, with a trend that does not appear to have the possibility of meeting the increasing demand in the future. Meanwhile, the study aimed at evaluating the indigenous knowledge of fuelwood and fuel value index (FVI) of ten selected sudano-sahelian fuelwood species and the results reveals a significant relationship between the indigenous knowledge and Fuel value index (FVI) of the ten selected fuelwood species. Higher FVI of 13.56MJ/m3 % 2 was obtained in A. leiocarpus followed by 6.61 MJ/m3 % 2 and 6.53MJ/m3 % 2 obtained in B. aegyptiaca and C. arereh meanwhile, lower energy fuelwood ranged from 0.11MJ/m3% 2 obtained in C. lamprocarpum. to 0. 85MJ/m3% 2, in S. birrea respectively. Meanwhile, A. leiocarpus, C. arereh, C. molle, and B. aegyptiaca were the most preferred and possessed good fuel quality. The indigenous knowledge might not be solely based on their fuel properties but availability and other possible reasons. Therefore, those fuelwood species identified with higher energy value can be incorporated in to fuelwood plantation establishment programs and those with lower energy value fuelwood should be allowed for environmental restoration and amelioration.